Analisis Nilai Tambah Ikan Asin Jambal Roti (Studi Kasus pada Kelompok Pengolah Pemasar Ikan di Desa Pangandaran, Kecamatan Pangandaran, Kabupaten Pangandaran, Jawa Barat) - Iwang Gumilar; Ananda Dwi Septian Septian; Rosnauli Oktavianti; Meyla Puspita Lestari; Nora Akbarsyah; Irfan Zidni; Ine Maulina; Astridya Syahada Putri Hermawan (Universitas Mataram, 2026)
Pangandaran has significant capture fisheries potential; however, fresh fish is highly perishable, requiring processing to increase its value. One prominent processed product is salted jambal roti fish, which plays an important role in the coastal economy. This study aims to analyze value added, technical production performance, and economic feasibility of processing businesses in Fish Processing and Marketing Groups (Poklahsar) in Pangandaran Village. The methods used include Hayami value-added analysis, cost-benefit analysis, and technical evaluation based on GMP, SSOP, and HACCP standards. The results show that the value added generated is Rp7,937.5/kg with a ratio of 19.8%, categorized as moderate. Economically, the business is feasible, with a profit of Rp1,235,069 per production cycle, profitability of 15.44%, and a Benefit-Cost Ratio of 1.18. The payback period is 0.23 years, with a break-even point of 12.95 kg and a unit production cost of Rp67,649/kg. However, technical performance remains low, with only 47% compliance with GMP, SSOP, and HACCP standards. In conclusion, the salted fish processing business is economically viable but requires improvements in technical practices and food safety systems to ensure sustainability.